An interrogation of the management strategies of the farmers and herdsmen conflict in Bayelsa State, Nigeria (2020)
Herdsmen and farmers conflict have become one of the major sources of insecurity and violence in Nigeria. This phenomenon has become widespread as virtually all the parts of the country is experiencing it, though in varying intensity. This paper assessed the approaches adopted in the management of the disenabling and destructive conflict by both the state and non-state actors in Bayelsa state, Nigeria. Data were collected fforn both primary and secondary sources. The United Nations Guiding Principles in Business and Human Rights was used as a tool of assessment. Findings revealed that the Bayelsa State government's management approach, which was deficient in terms of local ownership was less effective while the Bayelsa State Conflict Management Alliance approach, an initiative of the civil society, succeeded a great deal in reducing the conflict and restoring peaceful coexistence between the herdsmen and the farmers. This study established that the Bayelsa State Conflict Management Alliance approach succeeded due to its employment of the United Nations principles as its fulcrum. Consequently, this paper argued for the need for conflict interveners to involve the local people, as advocated in the United Nations Guiding Principles in Business and Human Rights, in their engagements in conflict.